Step
*
2
of Lemma
rnonzero_functionality
1. ∀x,y:ℝ.  ((x = y) 
⇒ rnonzero(x) 
⇒ rnonzero(y))
⊢ ∀x,y:ℝ.  ((x = y) 
⇒ (rnonzero(x) 
⇐⇒ rnonzero(y)))
BY
{ (Auto THEN InstHyp [⌜y⌝;⌜x⌝] 1 ⋅ THEN Auto) }
Latex:
Latex:
1.  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  rnonzero(x)  {}\mRightarrow{}  rnonzero(y))
\mvdash{}  \mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (rnonzero(x)  \mLeftarrow{}{}\mRightarrow{}  rnonzero(y)))
By
Latex:
(Auto  THEN  InstHyp  [\mkleeneopen{}y\mkleeneclose{};\mkleeneopen{}x\mkleeneclose{}]  1  \mcdot{}  THEN  Auto)
Home
Index